The Effect Of Application Of Wordwall Gamification Media In Accounting Learning On Vocational Students' Learning Interest In Sukoharjo - Theodora Fausta Ayu Gracia; Asri Diah Susanti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to examine the effect of the application of gamification learning media in accounting learning on the learning interests of students of SMKN Sukoharjo. The population of this study was the first grade students (class X) of Accounting and at SMKN Sukoharjo. The writer used random sampling technique to choose the sample. There were 36 students of X AKL B as the experimental class and 36 students of X AKL C as the control class. This study uses an experimental method with a quasi experimental approach. The technique of collecting the data was observation and questionnaire. The techniques of analyzing data were paired sample t-test, independent sample t-test, and N-Gain. The results of this study showed that there was a significant difference in students' learning interest. It was proven by the acquisition of paired sample t-test test results with a significance level of 0.000 <0.05. In the independent sample t-test test results obtained a significance value of 0.000 <0.05. In the N-Gain test results obtained in the experimental class showed a score of 0.38 or 0.38> 0.3. In addition, the average learning interest of students in the experimental class after treatment was 79.81 higher than the control class which had an average of 72.19. Thus it can be concluded that gamification media affected the students' learning interest of basic accounting learning at SMKN Sukoharjo.